THE ROLE OF HISTORICAL LANDSCAPES AND MONUMENTS IN DEVELOPING STUDENTS’ CREATIVE THINKING - Rustamova Farangiz Asqarbek qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the pedagogical potential of historical landscapes and monuments in fostering creative thinking among school students. It analyzes methods for integrating visual art and heritage sites into classroom activities to enhance imagination, critical analysis, and aesthetic perception. The study demonstrates that engaging with historical scenes and monuments helps students develop independent artistic expression, understand cultural and historical contexts, and strengthen problemsolving skills. Practical recommendations for educators are provided to implement these strategies effectively, promoting a holistic approach to art and history education.